EXPERIMENTAL INVESTIGATIONS AIMED AT THE FORMATION OF SILICON CARBIDE BY DIRECT APPLYING PULSED ELECTRICAL DISCHARGE MACHINING (Nonconventional Technologies Review, 2016)
The results of experimental investigations aimed at the formation of silicon carbide by direct applying pulsed electrical discharge machining (PEDM) are presented in this paper. The purpose was to form silicon carbide (SiC) that take place at temperature more than 2000°. The methodology of experimental investigations followed by analysis of theoretical and practical research results is presented in the paper. SEM and EDX analysis of the processed surfaces by direct applying PEDM are also presented. Silicon and graphite structures of different chemical content are investigated. These structures present a synthetic composite material, both ceramic and semiconductor, which possess exceptional properties. Formed silicon carbide behaves as a very hard material, chemically inert, resistant to oxidation.
Keywords: silicon; graphite; carbide; electrical discharges; oxidation